How Do Patients Think about Their Operation Scar after Cardiac Surgery? - Tanemoto, Kazuo; Kanaoka, Yuji; Kuroki, Keiichiro (Japanese Journal of Cardiovascular Surgery, 2000)
Because of the improved safety of cardiovascular surgical techniques, the small incision approach, called minimally invasive cardiac surgery (MICS), has recently been employed. In some cases of MICS, however, prolonged extracorporeal circulation time is required, and it is not minimally invasive in some aspects. It has been reported that the most prominent advantages of MICS is reducing the adverse consequences of conventional full-sternotomy, such as pain, bleeding and risk of mediastinitis, therefore it is helpful to reduce the period of hospitalization and costs. The small incision and cosmetic advantage is one of the objective advantages of MICS, so we interviewed 139 patients who underwent cardiac surgeries, to find out how they think of their operation scar. Most (61.9%) of the patients were not bothered by their scar, and the presence of keloid lesions mattered move than the size of their wound. What the patients considered to be most important were less pain after operation and shorter hospital stay, not to mention good results of the operation. The size and place of the wound ranked low in importance. It is important to be aware of the difference in thinking between the operative wound by patients and by the healthy medical staff. Furthermore it is important to recognize the difference between minimaly invasiveness and small incisions in cardiac surgery.